Does Schizophrenia Itself Cause Obesity? - Liang, Jiaquan; Cai, Yanshan; Xue, Xiongyan; Li, Xiaoling; Li, Zaifang; Xu, Caixia; Xie, Guojun; Yu, Yang (Frontiers in Psychiatry, 2022)
Background Schizophrenia(SC) is considered to be the most serious of all mental diseases. Some antipsychotics are associated with weight gain and metabolic abnormalities. Whether schizophrenia itself causes obesity remains uncertain. Methods We collected 185 first-episode drug-naïve SC and 59 healthy controls(HC) from the Third People’s Hospital of Foshan, Guangdong, China, and distinguished their course of disease, to understand the body mass index(BMI) and body fat metabolism of SC. Results We found that excluding the drug factors, the longer the course of SC, the more obvious the increase of BMI and the higher the proportion of obesity. BMI was positively correlated with age, course of disease, fasting blood glucose(FBG), low density lipoprotein(LDL), triglyceride(TG) and total cholesterol(TC), negatively correlated with high density lipoprotein(HDL). The results of regression analysis were further proof that age(B = 0.094, p＜0.001)，duration(B = 0.081, p = 0.002)，FBG(B = 0.987, p = 0.004)，TG(B = 0.918, p = 0.002) were the risk factors for the increase of BMI. HDL(B = -2.875, p＜0.001) was the protective factor. Conclusions SC itself can increase BMI and easily lead to obesity. We should pay more attention to the monitoring of blood metabolism indicators, so as to reduce the risk of obesity and improve their quality of life.